The Role of Information technology in Supporting Elementary School Student’ Literacy - Sopian Al Farizi; Dede Andrean; Yusuf Hendra Pratama (Secure And Knowledge-Intelligent Research in Cybersecurity And Multimedia (SAKIRA), 2025)
The advancement of information technology has significantly influenced the educational landscape, including efforts to enhance literacy among elementary school students. This study aims to analyze the role of information technology in fostering literacy at the primary education level through a literature review of national and international academic sources. The research method employed is a qualitative descriptive approach using library research. Data were collected from 24 relevant publications and analyzed thematically. The findings reveal that the integration of information technology through digital media such as e-books, educational videos, and online learning platforms positively contributes to improving students’ reading motivation, learning autonomy, and digital literacy skills. The role of teachers as facilitators in technology-based learning is pivotal to maximizing the benefits of ICT in literacy development. However, several challenges remain, including infrastructure limitations, low digital literacy among teachers, and unequal access to technology across regions. Therefore, the use of information technology in primary education requires well-planned and sustainable strategies to maximize its impact on student literacy improvement. These findings highlight the urgency for education policies that support digital transformation in elementary schools.